Species Differences in Microsomal Metabolism of Xanthine-Derived A1 Adenosine Receptor Ligands - Daniela Schneider; Dirk Bier; Marcus Holschbach; Andreas Bauer; Bernd Neumaier (MDPI AG, 2021)
Tracer development for positron emission tomography (PET) requires thorough evaluation of pharmacokinetics, metabolism, and dosimetry of candidate radioligands in preclinical animal studies. Since variations in pharmacokinetics and metabolism of a compound occur in different species, careful selection of a suitable model species is mandatory to obtain valid data. This study focuses on species differences in the in vitro metabolism of three xanthine-derived ligands for the A1 adenosine receptor (A1AR), which, in their 18F-labeled form, can be used to image A1AR via PET. In vitro intrinsic clearance and metabolite profiles of 8-cyclopentyl-3-(3-fluoropropyl)-1-propylxanthine (CPFPX), an established A1AR-ligand, and two novel analogs, 8-cyclobutyl-3-(3-fluoropropyl)-1-propylxanthine (CBX) and 3-(3-fluoropropyl)-8-(1-methylcyclobutyl)-1-propylxanthine (MCBX), were determined in liver microsomes from humans and preclinical animal species. Molecular mechanisms leading to significant differences between human and animal metabolite profiles were also examined. The results revealed significant species differences regarding qualitative and quantitative aspects of microsomal metabolism. None of the tested animal species fully matched human microsomal metabolism of the three A1AR ligands. In conclusion, preclinical evaluation of xanthine-derived A1AR ligands should employ at least two animal species, preferably rodent and dog, to predict in vivo behavior in humans. Surprisingly, rhesus macaques appear unsuitable due to large differences in metabolic activity towards the test compounds.